Analisis Daya Dukung Tiang Bor Berdasarkan Standard Penetration Test (Spt) Dan Hasil Reaction Pile - Sopian Sopian (The Faculty of Science and Technology, 2017)
An initial stage of Santika Hotel planning development Sukabumi, It’s located inBhayangkara Street, Gunung puyuh sub district had already made Uji KerucutStatis Analysis (sondir) Then It was continued with pile load’s analysis such asreaction pile (BP 108, H= 7 meter) for 120 tons workload. In order to fillinvestigation of land completely, then the foundation was in the project needanalysis of support capacity. Therefore, an author analyzed the case aboutcomparison result of drill pile between reaction pile result analysis with supportcapacity by practicing directly in the field using Standard Penetration Test (SPT)land tools. As for the purpose to be reached in this research is to know aboutresult of comparison drill pile with support capacity based on land penetration test and result of reaction pile to make sure the foundation safety. The methodused in support capacity calculation from result of observation is looking for Nresult. Calculation by using Meyerhof &Resee and Oneill Method. While thecalculation method by using reaction pile from Chin, Davisson, Mazurkiewcz areQa Lab > Qa React.Pile showed that the pile foundation save from collapseSupport capacity, Standart Penetration Test (SPT), Reactionpile, and Drill pile